Evaluation of Ayo Mondok Holiday Programme (Pesantren Kilat) Using The Alkin Model - Tomi, Tomi (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to evaluate the Ayo Mondok Holiday Programme (Pesantren Kilat) organised by Yayasan Darul Ulum Kleben using the Alkin Model. The programme is designed to introduce elementary/middle school students to pesantren life, instill Islamic values, and increase motivation to continue their education in pesantren. This study used a mixed method to analyse the three main components of the Alkin Model: inputs, processes, and outputs. The evaluation results show that the programme succeeded in improving participants' understanding of pesantren life, instilling Islamic values, and motivating them to further their religious education. The increase in the number of participants every year shows the high attractiveness of the programme. However, there were some challenges, such as adjustments to the schedule of activities and the need for additional training for the committee. Overall, the programme was effective in achieving its objectives. Recommendations for development include improving the programme structure, enhancing committee training, and continuous evaluation to ensure the sustainability of the programme's impact.